2020
DOI: 10.3390/info11020062
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs and Visual Attention during Urban, Highly Automated Driving—An Investigation of Potential Influencing Factors

Abstract: During highly automated driving, the passenger is allowed to conduct non-driving related activities (NDRA) and no longer has to act as a fallback at the functional limits of the driving automation system. Previous research has shown that at lower levels of automation, passengers still wish to be informed about automated vehicle behavior to a certain extent. Due to the aim of the introduction of urban automated driving, which is characterized by high complexity, we investigated the information needs and visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Design requirements stated by passengers after their first system experience often relate to the in-vehicle presentation of drivingrelated information and reveal their need for system transparency to decrease their uncertainty (Hartwich et al, 2020). Thus, even though there is no actual need to monitor a higher-level automated vehicle, many passengers still wish to not be completely excluded from the driving process (Ekman et al, 2018) and to receive information on the vehicle's driving behavior (Feierle et al, 2020). In the research tradition on trust in automation, it is well-established that informing users about the status and behavior of an automated system can improve their level of trust (Lee and See, 2004;Hoff and Bashir, 2015).…”
Section: Increasing the Transparency Of Automated Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Design requirements stated by passengers after their first system experience often relate to the in-vehicle presentation of drivingrelated information and reveal their need for system transparency to decrease their uncertainty (Hartwich et al, 2020). Thus, even though there is no actual need to monitor a higher-level automated vehicle, many passengers still wish to not be completely excluded from the driving process (Ekman et al, 2018) and to receive information on the vehicle's driving behavior (Feierle et al, 2020). In the research tradition on trust in automation, it is well-established that informing users about the status and behavior of an automated system can improve their level of trust (Lee and See, 2004;Hoff and Bashir, 2015).…”
Section: Increasing the Transparency Of Automated Vehiclesmentioning
confidence: 99%
“…So far, the implementation of users' information requirements and the user evaluation of resulting HMI concepts have mainly been focused on partially and conditional automated driving (SAE-Levels 2-3) due to the remaining human involvement in the driving task (Feierle et al, 2020;Oliveira et al, 2020). On these lower automation levels, an HMI serves specific safety-related purposes, such as supporting the human monitoring task or the transfer of vehicle control between human driver and automated driving system.…”
Section: Increasing the Transparency Of Automated Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown differences in informational needs according to the automation level [7], traffic situations [11], and the individual passenger [12], as well as differences in the extent to which passengers show changes in driver state, for example, fatigue [13]. Therefore, the aHMI should adapt to the traffic context, passenger's state, information needs, and the individual differences of the passenger to ensure sufficient trust, acceptance, and safety for the DAS.…”
Section: Automation Hmi (Ahmi)mentioning
confidence: 99%
“…No effects, however, were proven for workload and acceptance. According to Feierle et al [13], the degree of certainty with which the automation can cope with a situation is not relevant when no RtIs occur. However, with the ongoing research into automated driving with limited availability, concepts displaying the ability of the car to drive automated were assessed.…”
Section: Confidence Displaysmentioning
confidence: 99%